Consumers' perception on the quality of NFA imported rice in the Municipality of Zarraga - Jimenea, Nadja V.
This study on the consumers' perception on the quality of NFA Imported Rice was conducted mainly through surveys in seven barangays of Zarraga,Iloilo. The objective of this study is to provide a significant feedback to NFA Iloilo Field unit so that measures can be done to improve the services that local management will renderto its stakeholders especially the consumers on the quality of NFA Imported Milled Rice (IMR). Based on study results, 98% (or 82 ) of the respondents are aware that NFA Imported Milled Rice is distributed at low price during lean months. Although they have known the agency's distribution operation, only 58% had actually bought and consumed IMR during production shortfall or scarcity of staple cereal. The remaining 42% of the respondents alleged that IMR has undesirable odor, it causes their disease to recur, it causes them stomach disorders and others signified that they afford the price of local rice. When asked to compare the eating quality of IMR to local rice, 84% declared that local rice is better than IMR. However, for future incidence of rice and price hike, 77% of the respondents revealed that they are willing to buy IMR. Still, the remaining 23% prefer the high priced local rice or root crops as alternative to IMP even during rice crisis. The perception of the 97% of the respondents regarding the qualities of IMR showed to be unfavorable. They perceived NFA IMR to be of inferior quality compared to commercial or local rice.